Cover Image. Issue 2 (6th February 2022) - Shi, Yitian; Tong, Zian; Zhang, Yu; Si, Misi; He, Fuming
Abstract : COVER ILLUSTRATION: The cover image is based on the Original Article Microbial profiles of peri‐implant mucositis and peri‐implantitis: Submucosal microbial dysbiosis correlates with disease severity by Misi Si et al., https://doi.org/10.1111/clr.13880 .